Controlling the Security Objects Properties for Networks in Windows 2000 - Dhuha Abdullah; Abd-Alnaseer Ahmed (Al-Rafidain Journal of Computer Sciences and Mathematics)
Information security occupies a wide area in designing network operating systems. Windows 2000 was of the operating systems that offered great interest for network security, so it is recently considered as the most important network operating system because of the high extended capabilities in network security embedded in it. This search is devoted to the study of the network security in windows 2000. A special program for controlling the security properties for the main objects of the Windows 2000 database (Active Directory) has been built. ActiveX Data Object (ADO) is used for searching the Active Directory and ADSI interface for accessing security principal accounts. This software presents the likelihood of accessing the security properties of these objects to the level of flags and bits in the data structure of security properties elements.